The Role of Social Capital in the Development of Shrimp Cultivation Pond Business - Flora Meliana Siahaan; Amalliah Amalliah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Shrimp cultivation is a priority in the aquaculture sector, and the development of aquaculture in Indonesia to improve the national economy; something that cannot be ruled out is the element of social capital. This social capital is related to various forms of cooperation or collective action in society to achieve better life goals, which are supported by values, norms, trust, and networks. To overcome the various obstacles that arise in the implementation of the development and expansion of the shrimp pond business, group members or the community of Pedes District, Karawang Regency, cooperation and active participation from the community are needed. The component of social capital in the form of trust is the basis for forming social interaction. In addition to the trust that must exist between farmers, there is a desire to participate and form a network, both among fish farmers and with other parties such as investors and collectors or companies that accommodate their crops. So, social capital plays a role in developing shrimp farming in Karawang Regency. The data collection technique used is observation and in-depth interviews with a key informant who is an elder figure (star person) and three representatives of aquaculture farmers who have been cultivating for the last ten years so that primary data is obtained from informants regarding the role of social capital in developing aquaculture businesses. Shrimp Ponds in Pedes District, Karawang Regency.